PENGARUH PENDAPATAN ASLI DAERAH, LEVERAGE, UKURAN PEMERINTAHAN, DAN DANA PERIMBANGAN TERHADAP KINERJA KEUANGAN PEMERINTAHAN DAERAH PADA PROVINSI SUMATERA UTARA - Dessy Riani; Junita Putri Rajana Hrp (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2022)
This study aims to determine whether the effect of local revenue, leverage, government size, and balancing funds on the financial performance of local governments either simultaneously or partially in districts/cities in North Sumatra Province. The research method in this thesis is using quantitative research, with a total sample of 33 from 25 districts and 8 cities in North Sumatra Province which was conducted for the 2018-2020 period. The type of data used is secondary data. This data was obtained through the website www.bps.go.id. The data that has been collected was analyzed by data analysis methods which were first carried out by testing the classical assumptions before testing the hypothesis. Hypothesis testing in this study using multiple linear regression with F test and t test. The results show that simultaneously local revenue, leverage, government size, and balancing funds on the financial performance of local governments have a significant effect on the financial performance of local governments. Partially, the local revenue variable has a positive and significant effect on the financial performance of local governments. Partially, the leverage variable has a positive and significant effect on the financial performance of local governments. Partially, the variables of the size of the local government are leverage, the size of the government, and the balancing fund on the financial performance of the local government. Partially, the balancing fund variable has a positive and significant effect on the financial performance of local governments.